Risk of symptomatic venous thromboembolism following emergency appendicectomy in adults - Humes, David; Walker, Alex J.; Hunt, B.J.; Sultan, Alyshah Abdul; Ludvigsson, Jonas F.; West, Joe (John Wiley & Sons, Ltd, 2016)
BACKGROUND: Appendicectomy is the commonest intra-abdominal emergency surgical procedure, and little is known regarding the magnitude and timing of the risk of venous thromboembolism (VTE) after surgery. This study aimed to determine absolute and relative rates of symptomatic VTE following emergency appendicectomy.